Profesní portfolio v přípravném vzdělávání učitelů mateřských škol - Syslová, Zora; Píšová, Michaela; Rodová, Veronika; Grůzová, Lucie; Stadlerová, Hana (Masaryk University Press, 2024)
Title in English: Professional portfolio in the preparatory education of kindergarten teachers The publication is a study text intended for students of the Kindergarten Teacher and Preschool Pedagogy study programs. Its goal is to present the professional portfolio as an important part of one’s own professional development and reflectively conceived preparatory education of kindergarten teachers. It represents the summative and formative function of the professional portfolio and its role in the professional development of students and in the state final exam. The publication was created with the intention of helping students learn to systematically record and reflect on the process of becoming a teacher through creating and working with their own portfolio.